Działania ratownicze ochotniczych straży pożarnych podczas akcji ratowniczych organizowanych i prowadzonych przez Państwową Straż Pożarną - Filaber, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
There are several kinds of entities responsible for fire protection strictly related to public safety of the Republic of Poland: public administration organs and specialised units. Furthermore, fire protection is provided by non-government organisations and citizens themselves. The latter associate as, for example, members of volunteer firefighters who gather deliberately to take civil responsibility for both individual and local safety risked by fire and other dangers. The aim of this paper is to present the legal aspects of volunteer firefighters rescue actions and to indicate their position and significance in operations organised and managed by State Firefighters to provide fire protection of the Republic of Poland.
Keywords: ochrona przeciwpożarowa; strażacy ochotniczy; Państwowa Straż Pożarna; akcje ratownicze